Elaboración de un plan de marketing para la empresa la casa de las Mochilas de la ciudad de Loja. - Guacho Bagua, Luis Alfredo (2012)
In the management of the Company "The house of the backpacks" can settle down several problems among which can highlight the lack of incentives for clients, the personnel's qualification in attention to the client. These aspects are necessary that they are overcome to be able to optimize the profitability and growth of the company. For the development of the present work the methodology was continued that corresponds to a marketing plan, the same one that is important to determine if the company is administered in an appropriate way. He/she was also defined the internal and external conditions by means of the use of main FODA, those that it allowed us to know the situation of the company objectively. Inside this work he/she was also carried out an I diagnose situational, through the external analysis and I intern of the company information that served like base to apply in the hills to the internal and external actors of the same one. Then it was made the study and analysis FODA, with their wombs of valuation with the purpose of to quantify and to identify their potentialities like managerial limitations. According to this analysis FODA intended the implementation of 5 strategic objectives to improve the organizational, administrative structure and of management, which will be described next: To take advantage of the good location and the growth of the demand. To develop a countable system To elaborate a recruitment plan of personal. To elaborate suitable plans of marketing In definitive the total cost of this Plan of Marketing totals a value of $2.505,00 American dollars. Finally the conclusions and more convenient recommendations were made for this organization, to be better administratively, organizacionalment and in question to their services.